Resposta do olival intensivo e super-intensivo a dois regimes de rega: parâmetros fisiológicos, produção e qualidade - Coelho, R. (2012)
Olive grove irrigation has substantially increased in the past years on the region of Alentejo (southern Portugal). The correct determination of the plant water requirements is one of the key factors on the orchard management. This work evaluates the response of two varieties of Olea europaea, Cobrançosa in an intensive grove (hereafter named FEA) and Arbequina in a hedgerow orchard (hereafter named OSul), subject to two water regimes, the one usually practiced by the farmer (emitters with flow rate 1.6 or 2.3 l h-1 on FEA or OSul, respectively) and an excessive water supply on FEA or a deficit irrigation in OSul. The main water relation parameters, chlorophyll content and spectral emission were determined on adult and young leaves, at solar mid-day, three times over the year, spring, late summer and winter 2011. In October, fruits were harvested and total production, oil content and quality were assessed. The results show that in the intensive grove of Cobrançosa (FEA), water supply above the one practiced by the farmer did not improve fruit production neither oil content or quality. There were also no significant differences between the water relation parameters of plants subject to the two irrigation regimes. As to the hedgerow orchard of Arbequina (OSul), deficit irrigation induced lower production and also lower leaf water content, lower water potential and lower stomatal conductance at the end of summer and winter, although oil content and quality remained similar. Chlorophyll content and vegetation indexes were only occasionally affected by the irrigation regime. In both olive groves and irrigation regimes, oil quality was not affected, always attaining the characteristics of an extra virgin olive oil. This research continues in 2012.